Diversitas dan Komposisi Flora Paku (Pteridophyta) di Perkebunan Teh Nirmala Citalahab, Kecamatan Kabandungan, Sukabumi, Jawa Barat: Diversity and Composition of Pteridophytes at Nirmala Citalahab Tea Plantation, Kabandungan District, Sukabumi, West Java - Irawan, Afri; Maulana, Lana; Djuita, Nina Ratna; Ariyanti, Nunik Sri; Chikmawati, Tatik (Jurnal Sumberdaya Hayati, 2024)
Pteridophytes are able to live in a variety of habitats resulting in high species diversity. However, in monoculture vegetation such as tea plantations, species diversity can be reduced. This study aimed to compare the composition of the pteridophytes on the edge of the main road and the area in the tea garden at the Nirmala Tea Plantation, Kabandungan District, Sukabumi, West Java. Samples were collected using the exploratory method, then identified and observed for their morphological characteristics, and then the data were analyzed descriptively. The diversity of pteridophytes in the tea garden area (18 species) was lower than the main roadside tea plantation (25 species). Some species in the tea plantations were only found in the tea garden area (7 species) or on the side of the main roadside (14), and there were also species found in both locations (11 species). Pteridophytes in the study area is dominated by terrestrial ferns and the Polypodiaceae family. Soil moisture and wind speed are more influential factors on the diversity of pteridophytes than other abiotic factors measured. This result is new information on the diversity of fern in the Tea Plantation.